(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This article explores the significance of Big Data in the formation and development of the digital economy as one of the most crucial aspects of contemporary global transformation. The paper provides definitions of both the digital economy and Big Data, discussing their key characteristics (volume, variety, velocity, and veracity), as well as the primary sources of data. Big Data is analyzed as a central tool in the digital economy, contributing to enhanced decision-making, the automation of business processes, cost reduction, and the creation of new business models. Special attention is given to examples of Big Data applications across various industries: from consumer behavior analysis in retail to personalized medicine, from risk management in the financial sector to optimization of transportation and logistics processes. Additionally, the article addresses the challenges related to the use of Big Data, such as privacy issues, data security, challenges in processing and storage, and ethical concerns. In the concluding section, the article discusses the prospects of Big Data technologies within the digital economy, emphasizing the amplification of their influence through the integration of artificial intelligence, the development of cloud computing, and the expansion of the Internet of Things. The importance of integrating Big Data into public administration and business strategies in the context of digital transformation is highlighted. This article is intended for specialists in digital technologies, analysts, researchers, and the general public interested in the implementation of innovative technologies and the digital transformation of the economy.